Follicular wave emergence and fertility following estrogen based synchronization regimen in anestrus buffaloes (Bubalus bubalis) - BHAT, G R; DHALIWAL, G S; GHUMAN, S P S; HONPARKHE, M; GANDOTRA, V K (The Indian Journal of Animal Sciences, 2021)
The study was undertaken to study the follicular changes around the time of new wave emergence following estradiol-17ï¢ (E-17) + controlled internal drug release (CIDR) based synchronization in 30 anestrus buffaloes. The animals were divided in two Groups, viz. Group I and II. In Group I (n=20), on day 0 (beginning of experiment), buffaloes were administered CIDR device (1.38 g P4) and concurrently received 1.5 mg estradiol-17ï¢ in 1.5 ml canola oil (i. m.). On day 9, CIDR was removed and a prostaglandin (PG) 2 analogue (500 μg, i. m.) was administered. On day 11, buffaloes were administered gonadotropin releasing hormone (GnRH) analogue (20 μg, i.m.) and inseminated twice at 12 h and 24 h following GnRH injection. Group II (control, n=10) received the CIDR-based protocol except the administration of estradiol at the time of CIDR insert. Ovaries were examined for follicular wave emergence, ovulation of dominant follicles at estrus and subsequent conception at 45 days of insemination. The mean diameter of largest follicle was reduced from 8 mm (0th day) to 4 mm on the day of wave emergence (WE), i.e. day 4 in Group I but day 6 in control. The mean number of 4-5 mm follicle was 5.7 in Group I and 4.8 in control on the days of WE. Ovulation and conception rates achieved were 85 vs 60% and 47 vs 30% respectively. In conclusion the new wave emergence was induced earlier by estradiol-17ï¢ administered along with CIDR which ultimately resulted in more ovulation and conception rate in buffalo. Estrogen based protocols might be adopted to improve fertility in anestrum buffaloes.